2000
DOI: 10.1055/s-2000-7963
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Withdrawal Symptoms after Change to Sertindole in a Schizophrenic Patient

Abstract: A 30-year-old male patient with paranoid schizophrenia was on clozapine therapy for more than five years. Discontinuation of clozapine and an attempt to change his medication to sertindole has led to serious psychotic and somatic symptoms. After readministration of clozapine the psychotic symptoms rapidly disappeared. The patient was monitored by BPRS and PANSS positive and negative scale. Also clinical and labor parameters of the patient were monitored. The change of his medication from clozapine to sertindol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Ziprasidone, on the other hand, was well tolerated, improved mood and negative symptoms, but signs of a psychotic exacerbation occurred. Tapering off clozapine may lead to a withdrawal syndrome (Berecz et al, 2000;Shiovitz et al, 1996). Considering this danger we cross-tapered, reducing the clozapine dose slowly without noting typical somatic symptoms, extrapyramidal motoric dysfunction or psychotic symptoms within the critical time window.…”
Section: Discussionmentioning
confidence: 99%
“…Ziprasidone, on the other hand, was well tolerated, improved mood and negative symptoms, but signs of a psychotic exacerbation occurred. Tapering off clozapine may lead to a withdrawal syndrome (Berecz et al, 2000;Shiovitz et al, 1996). Considering this danger we cross-tapered, reducing the clozapine dose slowly without noting typical somatic symptoms, extrapyramidal motoric dysfunction or psychotic symptoms within the critical time window.…”
Section: Discussionmentioning
confidence: 99%
“…The dangers of abruptly withdrawing clozapine have been extensively reported (see Goudie [1] and Moncrieff [2]) but official advice concerning elective withdrawal (Approved Clozaril product information; Novartis Pharmaceuticals Australia, amended 12 June 2009) is simply that, in ‘planned termination’ of clozapine, ‘reducing the dose gradually over one to two weeks is recommended’. Previously (Stanitta et al [3] and Berecz et al [4]) suggested cross-tapering clozapine with an alternative antipsychotic over a few weeks.…”
mentioning
confidence: 99%